KINETICS OF THE HYDROGENATION PROCESS OF THE COAL AT MAMYT DEPOSIT - Zh.K. Kairbekov,; S.M. Suimbayeva,; I.M. Jeldybayeva,; M.Z.Yessenaliyeva , (Academic Scientific Journal of Chemistry, 2020)
For the first time, the kinetics of hydrogenation of the Mamyt coal in the presence of an oil pasting agent was studied by the method of equilibrium kinetic analysis. The developed program for calculating the rate constants allows to calculate kinetic dependences under given initial conditions and to carry out automated selection by the gradient method of optimal values of the rate constants k1-k7. The rate constants were optimized from the condition of minimum squared deviations between the experimental and calculated values of the mass fractions of the products of coal hydrogenation. The kinetic-thermodynamic picture of the process of coal hydrogenation at the Mamyt coal deposit obtained by us allows not only to get closer to the knowledge of the process mechanism, but also makes it possible to control the speed and selectivity of the process